A Drive Through Web 2.0: An Exploration of Driving Safety Promotion on Facebook™. Issue 1 (January 2013) - Apatu, Emma J. I.; Alperin, Melissa; Miner, Kathleen R.; Wiljer, David
This study explored Facebook™ to capture the prevalence of driving safety promotion user groups, obtain user demographic information, to understand if Facebook™ user groups influence reported driving behaviors, and to gather a sense of perceived effectiveness of Facebook™ for driving safety promotion targeted to young adults. In total, 96 driving safety Facebook™ groups (DSFGs) were identified with a total of 33, 368 members, 168 administrators, 156 officers, 1, 598 wall posts representing 12 countries. A total of 85 individuals participated in the survey. Demographic findings of this study suggest that driving safety promotion can be targeted to young and older adults. Respondents' ages ranged from 18 to 66 years. A total of 62% of respondents aged ≤24 years and 57.8% of respondents aged ≥25 years reported changing their driving-related behaviors as a result of reading information on the DSFGs to which they belonged. A higher proportion of respondents ≥25 years were significantly more likely to report Facebook™ and YouTube™ as an effective technology for driving safety promotion. This preliminary study indicates that DSFGs may be effective tools for driving safety promotion among young adults. More research is needed to understand the cognition of Facebook™ users as it relates to adopting safe driving behavior. The findings from this study present descriptive data to guide public health practitioners for future health promotion activities on Facebook™.